Employability Skills Perception of Employers and Student Interns - Valdez, Elaissa C.; Perez, Marjorie O.; Samson, Zaira Kristel T.; Valtoribio, Hannah Trisha C.; Pumihic, Mercedes B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Despite earning their degrees, many graduates still face a harsh truth—they're not meeting employer expectations. This study explores the skill gap between employers and student interns, focusing on Financial Management graduates from Nueva Vizcaya State University. Using a descriptive-quantitative method, data were gathered through survey questionnaires from 65 student interns and 15 Host Training Establishment (HTE) supervisors. Findings revealed both similarities and gaps in perceptions. For basic skills, employers placed more importance on communication, computer literacy, and being good with numbers than students. In hard skills, employers valued financial reporting, data analytics, risk assessment, and business acumen more than students did. For interpersonal skills, employers emphasized collaboration and negotiation, while students ranked them lower. In 21st-century skills, employers rated initiative and ICT literacy higher than students. Finally, regarding supplementary skills, employers gave greater importance to decision-making and data analysis — areas where students showed less awareness. The results indicate a disconnect between academic preparation and industry expectations, highlighting the need for stronger collaboration between schools and employers.